Spectrophotometric determination of reaction rates and kinetic parameters of a BAHD acyltransferase using DTNB (5,5'-dithio-bis-[2-nitrobenzoic acid]) - Sullivan, Michael L (Plant science : an international journal of experimental plant biology, 2018)
Published by Elsevier B.V.